TBLT and Portuguese as a Host language: analyzing learners? oral performance in terms of Outcome Achievement and investigating the task implementation process through the learners? and the teacher?s perspectives - Marcelino, Ana Flávia Boeing (2020)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2020.